Sex Differences in Long-Term Mortality and Functional Outcome After Rehabilitation in Patients With Severe Stroke - Scrutinio, Domenico; Battista, Petronilla; Guida, Pietro; Lanzillo, Bernardo; Tortelli, Rosanna (Frontiers in Neurology, 2020)
Objective: We sought to determine sex differences in outcomes in patients with severe stroke who had been admitted to inpatient rehabilitation. Methods: We studied 1,316 patients aged 18 to 99 (mean 72) classified as case-mix groups 0108, 0109, and 0110 of the Medicare case-mix classification system. These groups encompass the most severe strokes. Three outcomes were analyzed: (1) 3-year mortality from admission to rehabilitation; (2) combined outcome of transfer to acute care or death within 90 days from admission to rehabilitation; (3) functional outcome, including proportional recovery in motor functioning and good functional outcome as defined by achievement of a Functional Independence Measure (FIM)-motor score ≥65 points at discharge. Multivariable regression analyses were used to assess sex-difference in each outcome between women and men. The covariates examined included age, marital status, comorbidities, time from stroke onset to rehabilitation admission <30 days, ischemic stroke, dysphagia, neglect, motor FIM score at admission, and cognitive FIM score at admission. Results: Kaplan-Meier estimated 3-year mortality rate was 20.7% in women and 22.0% in men. The crude hazard ratio (HR) of death for women compared with men was 0.94 (95% CI 0.74–1.20). After adjustment for significant covariates, the HR of 3-year mortality was 0.73 (95% CIs 0.56–0.96; p = 0.025). Comorbidity, including diabetes, anemia, coronary artery disease, atrial fibrillation, and chronic obstructive pulmonary disease, significantly increased mortality risk by 49–88%. The incidence of the combined outcome was 8.3% in women and 8.4% in men. The crude HR of the combined end-point for women compared with men was 1.05 (95% CI 0.72–1.53). After adjustment for significant covariates, the HR was 0.95 (95% CIs 0.65–1.40; p = 0.810). Likewise, no significant difference in proportional recovery or in the rate of achievement of a good functional outcome between women and men was observed. Conclusion: Among patients admitted to inpatient rehabilitation after severe stroke, women and men had comparable crude mortality rates at 3 years. After multivariable adjustment, however, women had lower mortality risk. No sex-differences in the risk of being transferred to acute care or dying within 90 days from admission to rehabilitation or in responsiveness to rehabilitation were observed.